Appropriate assessment of ethnic differences in adolescent use of psychotropic medication: multilevel analysis of discriminatory accuracy. Issue 6 (1st November 2016) - Ivert, Anna-Karin; Mulinari, Shai; van Leeuwen, Willemijn; Wagner, Philippe; Merlo, Juan
ABSTRACT: Objective: In the present study, we used a multilevel approach to investigate the role of maternal country of birth (MCOB) in predicting adolescent use of psychotropic medication in Sweden. Design: Using the Swedish Medical Birth Register we identified all 428, 314 adolescents born between 1987 and 1990 and who were residing in Sweden in the year they turned 18. We applied multilevel logistic regression analysis with adolescents (level 1) nested within MCOBs (level 2). Measures of association (odds ratio) and measures of variance (intra-class correlation (ICC)) were calculated, as well as the discriminatory accuracy by calculating the area under the Receiver Operator Characteristic (AU-ROC) curve. Results : In comparison with adolescents with Swedish-born mothers, adolescents with mothers born in upper-middle, lower-middle and low-income countries were less likely to use psychotropic medication. However, the variance between MCOBs was small (ICC = 2.5 in the final model) relative to the variation within MCOBs. This was confirmed by an AU-ROC value of 0.598. Conclusions : Even though we found associations between MCOB and adolescent use of psychotropic medication, the small ICC and AU-ROC indicate that MCOB appears to be an inaccurate context for discriminating adolescent use of psychotropic medication in Sweden.